Rectification of nets of horizontal control to elaborate geographical chart - Santos Rodríguez, Ricardo (2012)
In order to establish the horizontal nets four contiguous quadrilateral ones were realized or in chain and ligatures to the national net by means of 4 geodesic points with base of exit in S.E.B. Conchán and whose coordinated geographical ones it measured itself to the system of global position geodesic GPS for 2 hours in every apex. Supported on these apexes one formed the net of the four quadrilateral ones, and for the compensation and adjustment by means of the mathematical hardware classic and verified with computers hardware of the formed figures, one raised the processes of classic or traditional geodesy and the process in block. It is observed that the error becomes bigger and bigger and concentrates on the central apexes of the net being the maximum changes in arranged in the apexes Pachacamac and Guayabo with -0.018m and -0.008m respectively, and indicates that the above mentioned apexes of the method in block are more on the South than of the classic method; where as the changes of the abscissas of the same apexes are more to the East for having 0.003 m and 0.003 m respectively, remaining demonstrated the displacement of the net in the method in block. Here it proposes to use the adjustment in block that is adapted for adjustments in netS, the same one that will serve to prepare planes of diverse applications of engineering and according to our reality.Also there compared the coordinated geographical ones and UTM of the apex Temple located in the Ruins of Pachacamac, with the work realized by the Company Consulting Miner and which values differ in the North in -0.006m, to the East in 0.0055m and in height in -0.28m; for the results, the present investigation has good reliability.